Prevention of neural tube defects in the UK: a missed opportunity. Issue 7 (17th December 2015) - Morris, JK; Rankin, J; Draper, ES; Kurinczuk, JJ; Springett, A; Tucker, D; Wellesley, D; Wreyford, B; Wald, NJ
Abstract : Objective: In 1991, the Medical Research Council (MRC) Vitamin Study demonstrated that folic acid taken before pregnancy and in early pregnancy reduced the risk of a neural tube defect (NTD). We aimed to estimate the number of NTD pregnancies that would have been prevented if flour had been fortified with folic acid in the UK from 1998 as it had been in the USA. Design: Estimates of NTD prevalence, the preventive effect of folic acid and the proportion of women taking folic acid supplements before pregnancy were used to predict the number of NTD pregnancies that would have been prevented if folic acid fortification had been implemented. Setting: Eight congenital anomaly registers in England and Wales. Main outcome measures: The prevalence of pregnancies with an NTD in the UK and the number of these pregnancies that would have been prevented if folic acid fortification had been implemented. Results: From 1991 to 2012, the prevalence of NTD pregnancies was 1.28 (95% CI 1.24 to 1.31) per 1000 total births (19% live births, 81% terminations and 0.5% stillbirths and fetal deaths ≥20 weeks' gestation). If the USA levels of folic acid fortification from 1998 onwards had been adopted in the UK, an estimated 2014 fewer NTD pregnancies would have occurred. Conclusions: Failure to implement folic acid fortification in the UK has caused, and continues to cause, avoidable terminations of pregnancy, stillbirths, neonatal deaths and permanent serious disability in surviving children.